Measuring the conformity level of the evaluation instruments in the BSE for indonesian language subject with the 2013 curriculum - Imam Safi'i; Ismi Salamah (BAHASTRA, 2021)
The purpose of this article is to describe the research findings regarding the conformity level of the evaluation instruments in the BSE for Grade IX of Junior High School in the academic year of 2019/2020 with the basic competencies in the 2013 Curriculum. The research method used in the research was content analysis, by matching each evaluation instrument in the BSE for Indonesian language subject for Grade IX of Junior High School in the academic year of 2019/2020 with the basic competencies of the 2013 Curriculum. The data analyzed were 77 evaluation instruments related to four teaching materials, namely exemplum text, critical response text, refutation text, and experimental record text. The results showed that the average conformity level of the evaluation instruments in the BSE for Indonesian language subject for Grade IX in the academic year of 2019/2020 was 89.70%. The average score indicates that the conformity level of the evaluation instruments in the BSE for Indonesian language subject with the 2013 Curriculum is very high. The results of this study can be used as an indicator of quality BSE assessment.